A Divalent PAMAM‐Based Matrix Metalloproteinase/Carbonic Anhydrase Inhibitor for the Treatment of Dry Eye Syndrome. Issue 5 (22nd December 2015) - Richichi, B.; Baldoneschi, V.; Burgalassi, S.; Fragai, M.; Vullo, D.; Akdemir, A.; Dragoni, E.; Louka, A.; Mamusa, M.; Monti, D.; Berti, D.; Novellino, E.; et al.
Abstract: Synthetic sulfonamide derivatives are a class of potent matrix metalloproteinase inhibitors (MMPI) that have potential for the treatment of diseases related to uncontrolled expression of these enzymes. The lack of selectivity of the large majority of such inhibitors, leading to the inhibition of MMPs in tissues other than the targeted one, has dramatically reduced the therapeutic interest in MMPIs. The recent development of efficient drug delivery systems that allow the transportation of a selected drug to its site of action has opened the way to new perspectives in the use of MMPIs. Here, a PAMAM‐based divalent dendron with two sulfonamidic residues was synthesized. This nanomolar inhibitor binds to the catalytic domain of two MMPs as well as to the transmembrane human carbonic anhydrases (hCAs) XII, which is present in the eye and considered an antiglaucoma target. In the animal model of an experimental dry eye, no occurrence of dotted staining in eyes treated with our inhibitor was observed, indicating no symptoms of corneal desiccation. Abstract : It's all in the delivery : The inhibitor shown here is a nanomolar, dendron‐based (PAMAM=poly(amidoamine) divalent sulfonamide that can bind gelatinase (MMP‐9), the most important matrix metalloproteinase (MMP) on the ocular surface, and the transmembrane human carbonic anhydrase XII, present in eyes and considered an antiglaucoma target. In an animal model of a dry eye, no evidence of corneal desiccation was observed in eyes treated with the inhibitor.